American Education and the Search for Equal Opportunity - Educational Policies Commission, Washington, DC.; Educational Policies Commission, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1965)
The first section of this position paper traces the background of the problem of equal opportunity for the culturally, economically, and psychologically disadvantaged (migrant farm laborers, mountain whites, Negroes, Puerto Ricans, American Indians, and Mexican Americans). The second section discusses ways and means of overcoming the problem through education (1) the role of the school--nursery and kindergarten, elementary and secondary education, adult and continuing education; (2) the education of teachers of the disadvantaged; and (3) school-community relations. The third section, "De Facto Segregation as a Special Problem," includes lists of principles and recommendations to govern the search for solutions to de facto segregation problems. (JS)
Availability: National Education Association, 1201 16th St., N.W., Washington, D.C. 20036 (Clothbound, $1.25; paper self-cover, $0.35).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: De Facto Segregation; School Role; Disadvantaged Youth; Educational Opportunities